The SciCommDiversity Travel Fellowship: The Challenge of Creating a Sustainable Intervention - Roca, Alberto I.; Coleman, Cynthia-Lou; Haelle, Tara S.; Lee, Danielle N. (Frontiers in Communication, 2020)
Diversifying a community requires outreach, recruitment, and retention which in this case targets the science communication (SciComm) workforce. Establishing a strategy to accomplish such diversification includes designing, launching, and sustaining the new intervention. Here we review the 6-year history of the DiverseScholar SciCommDiversity Travel Fellowship. This intervention was designed to build a community of minority science communicators that would interact with experienced professionals at the ScienceWriters conference. The travel fellowship reduces the financial burden of conference attendance while introducing the fellows to mentors who facilitate networking and knowledge-building during the event's professional development opportunities. The first two years of the fellowship were catalyzed by Idea Grants from the National Association of Science Writers – producers of the ScienceWriters event. Two strategies were used to engage potential fellowship applicants. First, we sought minority journalists interested in STEM topics who wished to extend beyond their standard reporting beats (tech, politics, etc). Such student and professional journalists were found by networking with and producing conference panels at the National Association of Black Journalists and the Native American Journalists Association annual events. For the second strategy, we found minority scientists who were interested in exploring how to convert their social media and blogging activities to professional writing/reporting careers. We attracted such individuals through our activities at annual conferences such as the Society for the Advancement of Chicanos and Native Americans in Science as well as the Annual Biomedical Research Conference for Minority Students. Overall, one particular challenge of an intervention is financial sustainability once catalytic (grant) funds end. Here, we describe our model for a sustainable and synergistic intervention that positions the SciCommDiversity Travel Fellowship within the overall program of DiverseScholar's doctoral recruiting services. The fellowship is now funded internally from advertising sales revenue from the DiverseScholar MinorityPostdoc.org career portal. The website, though, is more than just a job board since the travel fellows contribute original reporting to the online magazine. Thus, beyond just reducing financial barriers, the fellowship's mentoring and publishing opportunities can advance a fellow's entry into the SciComm profession.